Transcriptional response of the xerotolerant Arthrobacter sp. Helios strain to PEG-induced drought stress - Hernández-Fernández, Gabriel; Galán, Beatriz; Carmona, Manuel; Castro, Laura; García, José Luis (Frontiers in Microbiology, 2022)
A new bacterial strain highly tolerant to desiccation and to UV radiation has been isolated from the microbiome of solar panels. This strain showed a high xerotolerance in the exponential and the stationary phase of growth and it has been classified as Arthrobacter sp. Helios according to its 16S rDNA, positioning this new strain in the ‘Arthrobacter citreus group’. The complete genome of Arthrobacter sp. Helios consists in a single circular chromosome of 3,895,998 bp, with a 66% GC content and no plasmids. A total of 3,586 genes were predicted, of which 2,275 protein-encoding genes were functionally assigned. The genome analysis suggests that it is motile, ecologically versatile, capable of growing in a variety of carbon sources and well poised to respond to environmental stresses. Using PEG6000 to mimic arid stress conditions, we have studied the transcriptional response of this strain to matric stress when cells are cultured on media containing 10% (PEG10) and 35% PEG (PEG35). The transcriptomic analysis revealed that cells can be easily adapted to moderate matric stress (PEG10) by modifying the expression of a small number of genes to maintain a high growth rate, while a higher matric stress (PEG35) altered the expression of many more genes. Remarkably, these metabolic changes do not confer the cells a higher tolerance to desiccation, suggesting that mechanisms to support matric stress and desiccation tolerance are different. The peculiar observation that Arthrobacter sp. Helios seems to be permanently prepared to handle the desiccation stress makes it an exciting chassis for biotechnological applications.